In‐line phase shift tomosynthesis. Issue 8 (15th July 2013) - Hammonds, Jeffrey C.; Price, Ronald R.; Pickens, David R.; Donnelly, Edwin F.
Abstract : Purpose: : The purpose of this work is to (1) demonstrate laboratory measurements of phase shift images derived from in‐line phase‐contrast radiographs using the attenuation‐partition based algorithm (APBA) of Yan et al. [Opt. Express 18(15), – (2010)]10.1364/OE.18.016074, (2) verify that the APBA reconstructed images obey the linearity principle, and (3) reconstruct tomosynthesis phase shift images from a collection of angularly sampled planar phase shift images. Methods: : An unmodified, commercially available cabinet x‐ray system (Faxitron LX‐60) was used in this experiment. This system contains a tungsten anode x‐ray tube with a nominal focal spot size of 10 μ m. The digital detector uses CsI/CMOS with a pixel size of 50 × 50 μ m. The phantoms used consisted of one acrylic plate, two polystyrene plates, and a habanero pepper. Tomosynthesis images were reconstructed from 51 images acquired over a ±25° arc. All phase shift images were reconstructed using the APBA. Results: : Image contrast derived from the planar phase shift image of an acrylic plate of uniform thickness exceeded the contrast of the traditional attenuation image by an approximate factor of two. Comparison of the planar phase shift images from a single, uniform thickness polystyrene plate with two polystyrene plates demonstrated an approximate linearity of the estimated phase shift with plate thickness (−1600 rad vs −2970 rad). Tomographic phase shift images of the habanero pepper exhibited acceptable spatial resolution and contrast comparable to the corresponding attenuation image. Conclusions: : This work demonstrated the feasibility of laboratory‐based phase shift tomosynthesis and suggests that phase shift imaging could potentially provide a new imaging biomarker. Further investigation will be needed to determine if phase shift contrast will be able to provide new tissue contrast information or improved clinical performance.